2012
DOI: 10.21273/hortsci.47.5.580
|View full text |Cite
|
Sign up to set email alerts
|

Partial Leaf Chemical Profiles of a Desert Watermelon Species (Citrullus colocynthis) and Heirloom Watermelon Cultivars (Citrullus lanatus var. lanatus)

Abstract: Whiteflies [Bemisia tabaci (Gennadius)] and aphids [Aphis gossypii Glover and Myzus persicae (Sulzer)] are serious threats to watermelon by direct feeding and by transmitting viruses of important virus diseases. The desert watermelon Citrullus colocynthis (L.) has been shown to exhibit resistance to these insect pests and could be a useful source for breeding resistance into watermelon [ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…A detailed phytochemical characterization of the leaves, stems, and roots of C. colocynthis revealed the presence of different classes of metabolites—such as coumarins, hydroxycinnamic acid derivatives, flavan-3-ols glycosides, flavone glycosides, and tetracyclic triterpenes (Table 1)—as according to previous investigations [42,43,44]. These compounds, which have been indicated as responsible for antifungal activity against Aspergillus strains [38], were abundant in the analyzed extracts (Table 1).…”
Section: Resultssupporting
confidence: 80%
“…A detailed phytochemical characterization of the leaves, stems, and roots of C. colocynthis revealed the presence of different classes of metabolites—such as coumarins, hydroxycinnamic acid derivatives, flavan-3-ols glycosides, flavone glycosides, and tetracyclic triterpenes (Table 1)—as according to previous investigations [42,43,44]. These compounds, which have been indicated as responsible for antifungal activity against Aspergillus strains [38], were abundant in the analyzed extracts (Table 1).…”
Section: Resultssupporting
confidence: 80%
“…These two groups include compounds that may exert beneficial activities on human health. Flavonoids accumulated in leaf and seed tegument of C. colocynthis are mainly apigenin and luteolin derivatives, as also previously reported [ 17 , 18 ]. These aglycones, belonging to the flavone subclass, are known to play several positive activities on human well-being, as described in recent reviews [ 40 , 41 ]; studies performed on humans revealed that apigenin in particular seems to exert in vivo ameliorative effects in cognitive performances, reduces the anxiety disorder symptoms, and shows modest benefits against insomnia [ 42 ].…”
Section: Discussionsupporting
confidence: 79%
“…This plant is therefore regarded as a promising source for bioactives, to be used in both biocontrol strategies for crop protection and investigated for the design of new generation drugs [ 14 , 15 , 16 ]; despite the number of studies exploring the biological activities of crude and/or organic extracts from the most various organs of C. colocynthis , only a few reports describe the isolation and characterization of single chemical constituents. Detailed phytochemical characterizations of extracts from wild plants confirmed the presence of different classes of metabolites (coumarins, hydroxycinnamic acid derivatives, flavan-3-ols glycosides, flavone glycosides, and tetracyclic triterpenes) [ 17 , 18 , 19 ], that have been indicated as responsible for antifungal activity against Aspergillus strains [ 20 ]; more recently, esculetin, p-coumaric acid derivatives, orientin, vitexin, apigenin derivatives, epicatechingallate, and Cucurbitacins (E and I) have been reported as the major components characterizing chloroform and methanol leaves, stem, and root extracts that possessed an anti-aflatoxigenic effect on the phytopathogenic fungus Aspergillus flavus [ 12 ]. Due to the implications that these findings could have on the future development of new drugs—and their commercial use—any effort to fine-tune the possible propagation and cultivation methodologies for this particular plant species is desirable, as long as the maintenance of the relevant phytochemical features is assured.…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanisms contributing to the observed resistance to whitefly in C. colocynthis genotypes have yet to be fully elucidated. We recently reported on some differences in leaf chemical profiles between some C. colocynthis and some watermelon cultivars, but the role of the chemicals for whitefly resistance was not ascertained (Ogbuji et al, 2012). Resistance may be mediated by several factors including non-preference and the ability of a plant to repel or otherwise defend against the development of insect pest infestation such as was observed in PI 346082.…”
Section: Discussionmentioning
confidence: 99%